Standar Pelayanan Penumpang pada Saat Permintaan Tinggi di Terminal Terpadu Pulo Gebang - Yudhika Gultom; Elly Sinaga (Institut Transportasi dan Logistik Trisakti, 2020)
The objectives of the research are to identify and analyze circulation of passengers and services at PuloGebang Integrated Terminal waiting area during peak season. Pulo Gebang Integrated Terminal is the South-East Asia’s largest terminal, inaugurated in December 2016. The method used in this research was simple linear regression. The result shows that the value gap between the level of expectation and the level of performance is negative, with the correlation coefficient of 0,751 and coefficient of determination of 56,4%. The hypothesis test result shows 10,913 > 1,66, meaning that the quality of services has strong and positive effects towards passengers’ satisfaction at Pulo Gebang Integrated Terminal departure waiting area.